2018
DOI: 10.22175/mmb2017.10.0051
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Assessment of Lamb Loin and Leg from Australia, New Zealand, and United States

Abstract: Lamb was sourced from 3 countries [Australia (AUS), New Zealand (NZ), and United States (US)] representing 2 muscle types (semimembranosus and longissimus lumborum) to evaluate the palatability of lamb loin and leg chops according to US consumers (n = 360). For tenderness, flavor, and overall liking, there was an interaction detected between source country and muscle (P < 0.05). Overall, US loin chops had the highest (P < 0.05) consumer sensory scores, were rated the most acceptable (P < 0.05), and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In agreement with results from other authors [15,27,28], flavor liking was the major driver of lamb meat overall liking, followed by tenderness and juiciness. In general, the level of tenderness across the loin samples in this study was rated as high, supporting the lower impact of tenderness relative to flavor on overall liking scores.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with results from other authors [15,27,28], flavor liking was the major driver of lamb meat overall liking, followed by tenderness and juiciness. In general, the level of tenderness across the loin samples in this study was rated as high, supporting the lower impact of tenderness relative to flavor on overall liking scores.…”
Section: Discussionsupporting
confidence: 92%
“…The main contributors to meat flavor are the volatile compounds generated by lipid degradation and Maillard reactions of soluble components during cooking or through reactions between them [33]. Different studies have reported a positive relationship between overall liking and intramuscular fat or total muscle fat content in lambs [30,[34][35][36]. These reports contrast with the lack of correlation between intramuscular fat and overall liking observed in the present study for all consumers and for consumers grouped in cluster 1 and the negative correlation observed between overall liking and intramuscular fat in cluster 2 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while close to 70% of monthly consumers identified lamb as important in their diet (data not shown), the weekly consumption category who scored LL flavour and overall liking lower, actually had a higher proportion of appreciators, negating this theory. This negative response observed in the most frequent consumers of lamb in the American cohort (weekly; Table 1) could be attributed to a preference for locally sourced lamb, as more favourable eating quality scores have been observed for domestic products compared to imported Australian lamb [24]. However, similar to Australia and China, consumer numbers were very low (n = 10) for this group and as such should be interpreted with a degree of caution.…”
Section: The Effect Of Meat Consumption Habitsmentioning
confidence: 91%